MENAGIH REALISASI JANJI-JANJI PRESIDEN YANG PEDULI PERTANIAN - Sutawi, Sutawi (Jurnal Bestari, 2009)
The development of agriculture still bear on three broad agendas, those are firming of food tenacity, escalation of competitive potency, and farmer's welfare. Those three are not the new agendas in development of agriculture, but parts of president's promise that is unproved yet. Now, agriculture society waits and asks for the realization of what the elected president had promised of caring the agriculture aspect. Care means giving facilities, service, protection, advocate, empowerment, and support to agriculture sector and the farmer. The promises are only ca be realized by a president who has vision on it.